2017
DOI: 10.1111/bcp.13252
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of single and multiple doses of a novel mGlu2 agonist, a potential antipsychotic therapy, in healthy subjects

Abstract: Oral doses of LY2979165 up to 60 mg as a single dose and up to 400 mg given as multiple QD doses, using a titration regimen, were well tolerated with linear PK. Overall, these data support further clinical evaluation of LY2979165.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
(25 reference statements)
1
8
0
Order By: Relevance
“…These characteristics, such as the limited penetration into the CNS and the slow elimination from the CNS, likely arise from the hydrophilic property of MGS0008. A similar pharmacokinetic profile was also reported in a study examining LY2812223 in humans, the chemical structure of which resembles that of MGS0008 …”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These characteristics, such as the limited penetration into the CNS and the slow elimination from the CNS, likely arise from the hydrophilic property of MGS0008. A similar pharmacokinetic profile was also reported in a study examining LY2812223 in humans, the chemical structure of which resembles that of MGS0008 …”
Section: Discussionsupporting
confidence: 80%
“…A similar pharmacokinetic profile was also reported in a study examining LY2812223 in humans, the chemical structure of which resembles that of MGS0008. 24 The bioavailability after the oral administration of MGS0008 in monkeys was only 3.8%, whereas it was 78.1% in rats. Since MGS0008 was not metabolized in the preclinical species, the large species differences in oral bioavailability might be due to differences in the rates of its gastrointestinal absorption, such as transporter-mediated uptake in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Eli Lilly and Company discovered LY2812223 (Fig. 6), a mGluR2 agonist [136,137]. LY2812223 was found active in an animal model of psychosis, sensitive to mGluR2 [95,137].…”
Section: Metabotropic Glutamate 2 Receptor Agonist: Ly2812223mentioning
confidence: 99%
“…6), a mGluR2 agonist [136,137]. LY2812223 was found active in an animal model of psychosis, sensitive to mGluR2 [95,137]. Unfortunately, in the pharmacokinetic studies, LY2812223 showed a poor oral bioavailability (~ 4%).…”
Section: Metabotropic Glutamate 2 Receptor Agonist: Ly2812223mentioning
confidence: 99%
See 1 more Smart Citation